Early use of remote dielectric sensing after hospitalization to reduce heart failure readmissions. (18th December 2020) - Lala, Anuradha; Barghash, Maya H.; Giustino, Gennaro; Alvarez‐Garcia, Jesus; Konje, Swiri; Parikh, Aditya; Ullman, Jennifer; Keith, Brendan; Donehey, John; Mitter, Sumeet S.; Trivieri, Maria Giovanna; Contreras, Johanna P.; et al.
Abstract: Aims: Readmission after hospitalization for acute decompensated heart failure (HF) remains a major public health problem. Use of remote dielectric sensing (ReDS) to measure lung water volume allows for an objective assessment of volume status and may guide medical optimization for HF. We hypothesized that the use of ReDS would lower 30 day readmission in patients referred to rapid follow‐up (RFU) clinic after HF discharge. Methods and results: We conducted a retrospective analysis of the use of ReDS for patients scheduled for RFU within 10 days post‐discharge for HF at Mount Sinai Hospital between 1 July 2017 and 31 July 2018. Diuretics were adjusted using a pre‐specified algorithm. The association between use of ReDS and 30 day readmission was evaluated. A total of 220 patients were included. Mean age was 62.9 ± 14.7 years, and 36.4% were female. ReDS was performed in 80 (36.4%) and led to medication adjustment in 52 (65%). Use of ReDS was associated with a lower rate of 30 day cardiovascular readmission [2.6% vs. 11.8%, hazard ratio (HR): 0.21; 95% confidence interval (CI): 0.05–0.89; P  = 0.04] and a trend towards lower all‐cause readmission (6.5% vs. 14.1%, HR: 0.43; 95% CI: 0.16–1.15; P  = 0.09) as compared with patients without a ReDS assessment. Conclusions: ReDS‐guided HF therapy during RFU after HF hospitalization may be associated with lower risk of 30 day readmission.